Маленький ад для хакера: [повесть] / Петр Северцев - Северцев Петр (Русский бестселлер, 2000)
Экземпляры: ф. 10 (20131125) / Инвентарный номер: 38240 / Цена: 15.00 / Авт.знак: С 28 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6-44